Korelasi Status Nutrisi dengan Tingkat Kadar Hemoglobin Darah pada Anak Usia Sekolah Dasar Markidam di Desa Cilame Kabupaten Bandung - Oktorina, Lenny; Hakim, Fadhli Dharmansyach; Buntoro, Josep Dharmadi; Berbudi, Afiat; Ewangga, Bayu (Faculty of Medicine, Universitas Andalas, 2023)
Malnutrition has many adverse effects, including a decrease in hemoglobin levels, or known as anemia. Malnutrition caused by nutritional deficiencies can affect the decrease in hemoglobin levels or anemia. Objective: To determined the correlation between nutritional status and hemoglobin levels in Markidam elementary school-age children in Cilame Village Methods: This cross-sectional study uses primary data from research subjects who have agreed. The number of subject research that has been taken was 143 respondents. Anthropometric examinations using weight scales and microtoise were then carried out in a plotting process to determine the nutritional status of respondents. The hemoglobin level was used as a rapid diagnostic test tool with the Easytouch brand type GCHB. Spearman test to find out the results of this research hypothesis. Results: Â Hemoglobin levels did not have a significant correlation with nutritional status. This could be seen from the significance value (p-value) of 0,172, where this value is greater than 0,05. Conclusion: There is no correlation between nutritional status and hemoglobin level at the age of elementary school children.Keywords: anemia, hemoglobin, nutritional status